State of the Union Addresses - Eisenhower, Dwight D. (Dwight David), 1890-1969 (Salt Lake City, UT : Project Gutenberg, 2004)
"State of the Union Addresses" by Dwight D. Eisenhower is a collection of historic speeches delivered by the author, who served as President of the United States from the early to mid-20th century. The addresses, composed during the post-World War II era, reflect the political, social, and economic challenges of the time. Throughout these speeches, Eisenhower outlines his vision for America, focusing on national security, foreign policy, economic growth, and social justice. The opening of the collection provides an introduction to Eisenhower's first State of the Union address, delivered on February 2, 1953. In this address, he emphasizes the joint responsibility of Congress and the administration in addressing the expectations set by the American public. Eisenhower articulates key principles guiding his administration's approach to international relations, including the need for a united global front against communism, the importance of economic readiness, and the necessity of civil defense measures. He also addresses the importance of integrity and efficiency within the government, outlining the ambitious goals that would shape his presidency moving forward. (This is an automatically generated summary.)
Release date is 2004-02-01
Produced by James Linden. HTML version by Al Haines.
Keywords: Presidents -- United States -- Messages; United States -- Politics and government -- Sources